(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Since ancient times, health care profession is considered to be a noble profession in all parts of the world. It may be modern medicine or allopathy, homoeopathy, Ayurveda, Siddha, Unani, Chinese medicine, veterinary medicine or any other medication system prevalent in a local area. Whatever might be the name or techniques the basic purpose of all systems and practitioners is to alleviate sufferings and save life of the living beings. Since time immemorial medical practitioners were considered next to god and have always enjoyed respectable position in the society. With change in times, advance of technology, rising cost of health care, increasing social and legal awareness among public the image of doctors, perception of patients towards doctors as well as perception of doctors towards patients have undergone a change. Doctors and other healthcare workers no longer enjoy the respect and position that was once there, instead sometimes doctors are even equated to money making machines. This paper is an attempt to analyse the root cause of this change in perception as well as to study/highlight the professional and social threats for doctors and other health care workers due to this change in perception.